The Influence of Kinesthetic Learning Style on Student Learning Outcomes in Experience Based Vocational Learning at SMKN 7 Surakarta - Lathifah, Dea Nisrina Nur; Hidayati, Nurul (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study investigates the influence of kinesthetic learning style on student learning outcomes in experience-based vocational learning, focusing on the Broadcasting and Film Department at SMK Negeri 7 Surakarta. The research adopts a quantitative approach with an ex post facto design to examine the relationship between naturally occurring kinesthetic learning tendencies and students’ academic performance without experimental manipulation. Data were collected from all 106 students using a validated and reliable kinesthetic learning style questionnaire and documented learning outcome records, and were analyzed through prerequisite testing and simple linear regression. The findings reveal that kinesthetic learning style has a positive and statistically significant effect on student learning outcomes, indicating that students with stronger kinesthetic tendencies tend to perform better in practice-oriented vocational learning environments. The results indicate that kinesthetic learning style has a positive and significant effect on student learning outcomes, as evidenced by an F value of 62.508 with a significance level of < 0.001. The coefficient of determination (R²) shows that 16.9% of the variance in learning outcomes is explained by kinesthetic learning style, while the remaining variance is influenced by other factors. Future research is recommended to involve broader samples, additional influencing variables, and mixed-methods approaches to provide a more comprehensive understanding of learning outcomes in vocational education contexts.